Revizija kronologije cerkvenih dostojanstvenikov na Primorskem - Mihelič, Darja (Zgodovinski časopis, 2005)
Based on the testimonies given in the lawsuit concerning the oil tithe in Piran (1201-1207), with the bishop of Koper on one side and the people of Piran and their clergy on the other, the article provides additional data on the lists and chronological order of the office of certain church dignitaries in the dioceses of Trieste and Koper.
Keywords: cerkvena zgodovina; pravna zgodovina; cerkveni dostojanstveniki; Piran; 13.st.